Improving Students Speaking Skill Through Podcast at X MIPA 2 Students OF SMAN 1 Rejoso - Sujono, Sujono (Dharma Pendidikan, 2022)
The purpose of the study are to find out student’s speaking skill before and after taught by using podcast media then to analyze the significant different on students’ speaking skill before and after taught by using podcast media in the teaching speaking. This research is Quasi- Experimental with one group pre- test, post- test. The research was done at SMAN 1 Rejoso for the academic year 2021/2022, by using population whole tenth grade, the sample used by the researcher is the class X-MIPA 2, that consists of 36 students. The technique of sampling is using purposive sampling. The collecting data in this research by using test. The technique of analysis data used to analyze the data in this research is Mean, Median, Mode, standard deviation and T test. Based on the results of the test scores, students showed an average pre-test score of 49 and post-test 80, for the t-count 27, while the t-table was 1,690, then t-count>t-table, which means Ho is rejected and Ha be accepted. So "there is a significant difference before and after using Podcast Media to improve students’ speaking skill at the tenth grade of SMAN 1 Rejoso in the Academic Year of 2021/2022”.